Efeitos da estimulação transcraniana por corrente contínua associada ao treino de mobilidade com realidade virtual sobre o equilibrio estático e funcional de crianças com paralisia cerebral: ensaio clínico controlado aleatorizado, duplo cego - Lazzari, Roberta Delasta (2015)
Purpose: To investigate the effects of transcranial direct current stimulation in the primary motor cortex, associated with mobility training with virtual reality on the static and functional balance of children with cerebral palsy (CP). Materials and Methods: The population sample that was part of this project consisted of 24 children with CP between 4 and 12 years old. The children were divided randomly into two groups (control group: mobility training with virtual reality and use transcranial stimulation placebo; Experimental Group: mobility training using virtual reality and transcranial stimulation active) and evaluated at four different times (pre -intervention, immediately after the first session, after the intervention and one month after intervention). The static balance was evaluated by force platform in four conditions: feet flat on the platform with open eyes, feet on the platform with eyes closed, feet in the open foam eyes, feet foam eyes closed for 30 seconds each. The Functional Balance was measured by Pediatric Balance Scale(PBS) and Timed Up and Go(TUG). Results: The analysis of the immediate effect of treatment with transcranial Direct Current Stimulation (tDCS) only sway velocity showed a significant interaction. In the analysis of the effects of the training area, Center of Pressure (COP) speed and frequency presented significatia interaction as well as the EEP and TUG Conclusion: It is suggested that tDCS interferes with the static and functional balance of children with CP.